Tribological self-repairing behavior in ATP/Al composites: An orthogonal experimental study on attapulgite mineral effects - Z. Yang; Z.G. Xing; H.L. Yu; G. Jin; Y.L. Yin; Z.Y. Song; X.F. Cui; W. Zheng; J.T. Gong; F.Y. Zhang (Journal of Materials Research and Technology)
The introduction of self-repairing functional materials effectively improves the tribological properties of metals by in-situ repairing of micro-damage on worn surfaces during friction. In this work, attapulgite (ATP)-reinforced Al matrix composites (ATP/Al) were fabricated via spark plasma sintering (SPS) using natural ATP minerals and Al powder as raw materials. The tribological performance of ATP/Al-steel sliding pairs under oil-lubricated conditions was investigated using a three-level four-factor orthogonal experimental design on an SRV-IV tribometer. Comparative analysis revealed that the composite materials exhibited reductions of 15.38–66.87 % in friction coefficient, 21.6–54.68 % in wear volume, and 10.5–39.71 % in counterpart steel ball wear scar diameter compared to pure Al sintered counterparts. The order of importance that affected the friction-reducing performance of the composites was load, ATP content, sliding time, and frequency, whereas the order of the anti-wear property was sliding duration, ATP content, load, and frequency. The frictional mechanochemical effect induces the in-situ construction of a self-repairing layer, composed of binary and ternary metal oxides, ceramics, ATP phase transformation products, and graphite, on the worn surface. The in situ formed self-repairing layer exhibits dual functionality: (1) high hardness ensuring mechanical durability, and (2) shear-induced graphitization providing solid lubricity, synergistically reducing friction and wear across sliding interfaces.